Acupuncture for Rehabilitation After Total Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Chen, Zehua; Shen, Zhen; Ye, Xiangling; Xu, Yanfei; Liu, Jinqing; Shi, Xiaodong; Chen, Guoqian; Wu, Jiatao; Chen, Weijian; Jiang, Tao; Liu, Wengang; Xu, Xuemeng (Frontiers in Medicine, 2021)
Background: There is increased interest in acupuncture to promote postoperative rehabilitation, but the effectiveness of acupuncture for rehabilitation after total knee arthroplasty (TKA) remains controversial. Objective: To investigated the effect of acupuncture on rehabilitation after TKA. Methods: Database searches of PubMed, EMBASE, CINAHL and China National Knowledge Infrastructure (CNKI) were conducted to obtain articles published until August, 2020. All identified articles were screened and data from each included study was extracted independently by two investigators. Meta-analysis was performed to examine the effect of acupuncture on pain, range of knee motion, function and nausea/vomiting after KOA. Results: A total of nine randomized clinical trials were included according to the inclusion and exclusion criteria in the review. Compared to routine treatment, acupuncture combining of routine treatment showed a significantly greater pain reduction at postoperative hour 8, 12, 24, and 48, whereas no statistically significant improvement in postoperative pain at 4h, 7d, 14d, and more than 21d. Meanwhile, no significant difference was observed between the acupuncture group and control group after surgery. However, we found that, after TKA, there was a significant improvement in function between the two groups, and acupuncture group had a significantly lower percentage of nausea/vomiting than control group. Conclusions: Acupuncture, as a supplementary treatment, could improve function, decrease pain only at 4h to 24h and reduce nausea/vomiting after TKA, whereas no efficacy for ROM of knee, and pain reduction was found at more than 7 days after surgery. More large-scale and high-quality studies are warranted.